Human Resource Quality Improvement Strategy Using Fuzzy Logic in the Mojokerto Footwear Industry as an Effort to Restore the Competitiveness of Local Brands - setyaasih, setyaasih; Nova Ashriana, Ahfi; Agustina, Ratna (Jurnal Manajemen dan Inovasi (MANOVA), 2026)
Objective – This study aims to develop a strategy for improving HR quality in the Mojokerto footwear industry using a fuzzy logic approach as the analytical method, in order to identify priority competency dimensions that most significantly influence the competitiveness of local brands Design/methodology/approach – A quantitative approach was employed, utilizing fuzzy logic to analyze the prioritization of HR dimensions. Findings – The findings indicate that the implementation of fuzzy logic enables a more precise mapping of HR competencies, both strengths and weaknesses, compared to traditional evaluation methods. Research limitations/implications – This research was only conducted in the local footwear industry in Mojokerto. as a further study recommends the need for integrated human resource development policies between local governments, industry associations, and shoe business players in Indonesia Practical implications – This study offers practical contributions by providing evidence-based recommendations for improving training strategies, designing vocational curricula, and implementing competency development programs aligned with the needs of the local footwear industry. Originality/value – These findings underscore that strengthening HR capacity through practical skills and innovation is essential for restoring the competitiveness of local brands in both domestic and international markets.